Development, Use, and Impact of a Global Laboratory Database During the 2014 Ebola Outbreak in West Africa. (18th May 2017) - Durski, Kara N.; Singaravelu, Shalini; Teo, Junxiong; Naidoo, Dhamari; Bawo, Luke; Jambai, Amara; Keita, Sakoba; Yahaya, Ali Ahmed; Muraguri, Beatrice; Ahounou, Brice; Katawera, Victoria; Kuti-George, Fredson; et al.
Summary: The usefulness and value of a multifunctional global laboratory database is far reaching, with uses including but not limited to informing local outbreak interventions, developing global outbreak response strategies, virtual biobanking, and disease forecasting. Abstract: Background: The international impact, rapid widespread transmission, and reporting delays during the 2014 Ebola outbreak in West Africa highlighted the need for a global, centralized database to inform outbreak response. The World Health Organization and Emerging and Dangerous Pathogens Laboratory Network addressed this need by supporting the development of a global laboratory database. Methods: Specimens were collected in the affected countries from patients and dead bodies meeting the case definitions for Ebola virus disease. Test results were entered in nationally standardized spreadsheets and consolidated onto a central server. Results: From March 2014 through August 2016, 256343 specimens tested for Ebola virus disease were captured in the database. Thirty-one specimen types were collected, and a variety of diagnostic tests were performed. Regular analysis of data described the functionality of laboratory and response systems, positivity rates, and the geographic distribution of specimens. Conclusion: With data standardization and end user buy-in, the collection and analysis of large amounts of data with multiple stakeholders and collaborators across various user-access levels was made possible and contributed to outbreak response needs. The usefulness and value of a multifunctional global laboratory database is far reaching, with uses including virtual biobanking, disease forecasting, and adaption to other disease outbreaks.